Hedonic behavior in Shopee live shopping: social media marketing, celebrity endorser, and e-WOM on impulse buying - Lestari, Fitri Amanda; Hayadi, Ilsya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This study aims to investigate the influence of social media marketing on impulsive buying behavior and hedonic behavior, and whether hedonic behavior can mediate the relationship between Social media marketing and impulsive buying behavior. his research follows a quantitative-explanatory approach and specifically targets consumers actively participating in Shopee Live Shopping. The population size remains indeterminate, and the sample size is determined using purposive sampling techniques. the study aims to gather responses from 345 individuals. SEM-PLS method is used in this research and employed SmartPLS 4 for data processing. In this study, the significant relationships between Social Media Marketing, Celebrity Endorser, E-WOM, and Impulse Buying Behavior mediated by Hedonic Behavior have been discussed. The research findings indicate that marketing factors such as social media campaigns, celebrity endorsers, and positive consumer reviews play a crucial role in shaping impulsive buying behavior. These results align with The Theory of Planned Behavior, which explains that individual intentions play a key role in shaping consumer behavior.